Voices of Young Mothers on Relational Issues Leading to Out-of-Wedlock Pregnancy and its Protective Measures: A Qualitative Exploration - T, Hizlinda; MI, Noriah; W, Suzaily; O, Khairani; S, Harlina Halizah; Koon T, Susan Mooi; A, Aishah; T, Noorlaili (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Adolescents learn through experimenting and interactions with others. Experimenting romance and sexuality issues if not properly guided, can result in an out-of-wedlock unplanned pregnancy. This study aims to explore factors leading to out-of-wedlock pregnancy among pregnant teenagers and factors that may prevent such occurrence. MATERIALS AND METHODS: Two in-depth interviews (IDI) and two focus group discussions (FGD) were conducted in this qualitative study. The study involved 22 participants from a local governmental body shelter home in Peninsular Malaysia. Interviews were audio-recorded and transcribed verbatim. Thematic analysis was used for data analysis. RESULTS: Three salient relationship themes that led to teenage pregnancy were i) an enjoyable relationship with peers, ii) poor family relationship, and iii) intimate relationship with boyfriends. Some of the proposed ways that may protect teenagers from pregnancy include i) careful selection of friends, ii) controlling the desire in risky experimentation, and iii) wiser use of smartphones or/and social media. CONCLUSION: Relational issues with parents, peers and boyfriends are important factors as it could lead to out-of -wedlock pregnancy among adolescents and youths. It is also necessary for the current educational system to emphasize on building positive relationships with peers, being more assertive, and the safe use of social media among youths.